An open prospective study on the efficacy of Navina Smart, an electronic system for transanal irrigation, in neurogenic bowel dysfunction. - Anton Emmanuel; Ines Kurze; Klaus Krogh; Maria Elena Ferreiro Velasco; Peter Christensen; Giuilio Del Popolo; Gabriele Bazzocchi; Claes Hultling; Brigitte Perrouin Verbe; Ralf Bothig; Thomas Glott; Miguel Angel Gonzalez Viejo (PLoS ONE)
Background Transanal irrigation (TAI) has emerged as a key option when more conservative bowel management does not help spinal cord injured (SCI) individuals with neurogenic bowel dysfunction (NBD). Aim To investigate the short-term efficacy and safety of an electronic TAI system (Navina Smart) in subjects with NBD. Design We present an open, prospective efficacy study on Navina Smart, in individuals with NBD secondary to SCI, studied at three months. Population Eighty-nine consecutive consenting established SCI individuals (61 male; mean age 48, range 18-77) naïve to TAI treatment were recruited from ten centres in seven countries. Subjects had confirmed NBD of at least moderate severity (NBD score ≥10). Methods Subjects were taught how to use the device at baseline assisted by the Navina Smart app, and treatment was tailored during phone calls until optimal TAI regime was achieved. The NBD score was measured at baseline and at three months follow up (mean 98 days). Safety analysis was performed on the complete population while per protocol (PP) analysis was performed on 52 subjects. Results PP analysis showed a significant decrease in mean NBD score (17.8 to 10, p<0.00001). In subjects with severe symptoms (defined as NBD score ≥14), mean NBD scores decreased (19.4 to 10.9, p<0.0001). The number of subjects with severe symptoms decreased from 41 (79%) subjects at baseline to 16 (31%) at three months follow-up. Device failure accounted for the commonest cause for loss of data. Side effects possibly related to the device developed in 11 subjects (12%). Discontinuation due to failure of therapy to relieve symptoms was reported by 5 subjects (6%). Conclusion Navina Smart is effective for individuals with NBD, even those with severe symptoms; long-term data will follow. Whilst there were some device problems (addressed by the later stages of subject recruitment) the treatment was generally safe. Clinical trial (ClinicalTrials.gov number NCT02979808).